How do you use the quadratic formula to solve #x^2+2x=4x#?

1 Answer
May 7, 2017

Answer:

For #ax^2+bx+c=0#, the quadratic formula is #x=(-b+-sqrt(b^2-4ac))/(2a)#.

Explanation:

First we need to get the equation to standard quadratic form by subtracting 4x from both sides:
#x^2-4x+2x=0# which we can simplify by combining like-terms
#x^2-2x=0#
Here we can see that according to the standard quadratic form, a=1, b=-2, and c=0.
By plugging these values into the quadratic formula, #x=(-b+-sqrt(b^2-4ac))/(2a)#
#x=(-(-2)+-sqrt((-2)^2-4*1*0))/(2*1)#
#x=(2+-sqrt(4))/2#
#x=(2+-2)/2#
#x=(1+-1)/1#
so #x=0# or #x=2#